PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP - Azizah, Nur (Jurnal Edukasi dan Penelitian Matematika, 2023)
Achievements/objectives of mathematics subjects include mastery of understanding mathematical concepts that students need to have. In fact, the ability of class VIII students of SMPN 2 Koto XI Tarusan in this regard is still relatively low. The cause of this is learning that is still focused on educators. To overcome this, the NHT type cooperative model in learning can be used as a solution. Quasi-experimental is a type of research that uses a non-equivalent posttest -only control group design. Meanwhile, 94 students in class VIII SMPN 2 Koto XI Tarusan make up the population. In selecting  sample, the researcher used a simple random sampling method. Class VIII.1 was chosen as the experimental class and class VIII.2 was chosen as the control class. Based on the hypothesis test with a significant level of  = 0.05 and obtain a P-value = 0.000. This can be interpreted as a P-value <  = 0.05 causes  to be rejected. This research concludes that the ability to understand mathematical concepts of students who study with the NHT cooperative learning model is better than students who learn with the direct learning model in class VIII SMPN 2 Koto XI Tarusan.. Keywords– Ability to Understand Mathematical Concepts, NHT Type Cooperative Learning Model, Direct Learning.